La rotación del personal y su relación con la calidad del servicio en el Hospital III Iquitos de EsSalud 2024 - Rojas Palacios, Johanna Stephania (2025)
The objective of this research was to determine the relationship between staff turnover and service quality at Hospital III Iquitos de Essalud 2024. The research was applied with a quantitative approach, with a non-experimental and correlational design. The population was made up of 300 collaborators, using non-probabilistic sampling which allowed us to know the sample that was made up of 120 collaborators. For the application of data collection, a questionnaire was used for each variable measured in its dimensions and indicators, which was provided to the collaborators. The results showed a Cronbach Alpha of 0.785 applied to both variables. This analysis was carried out using the Spss V. 26 statistical program. Concluding in this way that staff turnover and service quality are strongly and significantly directly related to a correlation of Spearman's rho of 0.891 with a significance of p=0.030.